Prognostic impact of HER2-low expression in triple-negative breast cancer of high-grade special histological type and no special type. - Claudia Grosse; Petar Noack; Alexandra Grosse; Heike Kathleen Schwarz; Peter Schrenk; Heike Frauchiger-Heuer; Rupert Langer; Zsuzsanna Varga (PLoS ONE)
Interest in HER2-low breast cancer has grown in recent years due to advancements in novel anti-HER2 antibody-drug conjugates. This study examined the impact of HER2-low expression on survival outcomes in triple-negative breast cancer (TNBC) of high-grade special histological type (ST) and no special type (NST) and investigated the prognostic significance of TNBC subtype (high-grade ST vs. NST) within HER2 0 and HER2-low expression subgroups. Clinicopathological and survival data of 504 patients with stage I-III TNBC, with or without neoadjuvant chemotherapy (NAC), were analyzed, including 400 patients with TNBC NST and 104 patients with high-grade TNBC ST. HER2-low status was not identified as an independent prognostic factor for survival in the overall cohort, nor within the high-grade TNBC ST and TNBC NST subgroups. Among patients who did not receive NAC, TNBC subtype (high-grade ST vs. NST) was independently associated with DDFS and DFS in the HER2 0 subgroup, but not in the HER2-low subgroup. Patients with HER2 0 high-grade TNBC ST exhibited significantly worse OS (p = 0.008), DDFS (p < 0.001), and DFS (p < 0.001) compared to those with HER2 0 TNBC NST. Among patients with either HER2 0 or HER2-low tumors treated with NAC, no significant survival difference was observed between high-grade TNBC ST and TNBC NST. These findings suggest that the prognostic impact of TNBC subtype (high-grade ST vs. NST) on survival outcomes may be modulated by HER2 status in a subset of TNBC patients.